Diaphragmatic crural eventration - Sivakumar K (Wolters Kluwer Medknow Publications, 2008)
Aim: We evaluated patients with gastric volvulus secondary to diaphragmatic pathology. Materials and Methods: Eight patients (5 males and 3 females) presented to the author in a tertiary care center during 1997-2006 were analyzed in terms of age, sex, symptomatology, diagnosis and predisposing factors. Observations: Six had an acute presentation and rest had chronic symptomatology. The two patients who had total gangrene stomach died postoperatively and one patient died preoperatively due to aspiration. All the cases presented with acute symptoms had diaphragmatic pathology, and out of these, three cases had the specific entity, which is named as diaphragmatic crural eventration. Conclusions: Diaphragmatic crural eventration is characterized by the defective development of the right crus of diaphragm, and this is embryologically significant as the right crus and ligaments of the stomach develop from dorsal mesoesophagus and mesogastrium. The author recommends a closer look for this defect of diaphragm while operating a case of gastric volvulus.